Women's income contribution and its effect on food consumption: An evidence from Aceh Province, Indonesia - Suriani, Nisa; Noviar, Helmi (Publisher of Widyagama University of Malang (UWG Press), 2022)
Consumption of each society is closely related to micro and macro conditions, as the income received by each community will affect their lifestyle patterns. The higher the income, the greater the expenditure on food and non-food consumption. Women have considerable potential in contributing to income, especially in poor households, but women do not stand out and claim that they are the main support in providing the economy for the family. The purpose of this study is to analyse the effect of women's income in the short and long term and predict food consumption in Aceh Province in the future. The model analysis used in this study is a partial adjustment model with panel data from 23 cities/regencies in Aceh Province. The next step is to predict the level of consumption in each district and city, and make a regional analysis based on the geographical conditions of this province in four regional divisions to get an aggregate depiction of the differences in food consumption levels in each region. Regional development strategy should be made based on the estimation results and prediction of consumption levels and women's empowerment in development participation in this province in the future for food security development program.JEL Classification C53; D16; R10